An mTOR siRNA‐Loaded Spermidine/DNA Tetrahedron Nanoplatform with a Synergistic Anti‐Inflammatory Effect on Acute Lung Injury. Issue 11 (25th February 2022) - Huang, Chaowang; You, Qianyi; Xu, Jing; Wu, Di; Chen, Huaping; Guo, Yuhang; Xu, Jiancheng; Hu, Mingdong; Qian, Hang
Abstract: Acute lung injury (ALI) is characterized by severe inflammation and damage to the lung air–blood barrier, resulting in respiratory function damage and life‐threatening outcomes. Macrophage polarization plays an essential role in the occurrence, development, and outcome of ALI. As drug carriers, self‐assembled DNA nanostructures can potentially overcome the drawbacks and limitations of traditional anti‐inflammatory agents owing to their nontoxicity, programmability, and excellent structural control at the nanoscale. A small interfering RNA (siRNA) and drug dual therapy nanoplatform are proposed and constructed here to combat ALI. The nanoplatform consists of a spermidine‐assembled DNA tetrahedron and four mammalian target of rapamycin siRNAs. Spermidine serves as a mediator of drug delivery vehicle synthesis and a drug that alters macrophage polarization. Both spermidine and siRNA exert anti‐inflammatory effects in vitro and in vivo by regulating the macrophage phenotype. More importantly, these factors exhibit a synergistic anti‐inflammatory effect by promoting macrophage autophagy. For the first time, an anti‐inflammatory dual therapy strategy that uses self‐assembled DNA nanostructures as nontoxic, programmable delivery vehicles is proposed and demonstrated through this work. Future work on utilizing DNA nanostructures for the treatment of noncancerous diseases such as ALI is highly promising and desirable. Abstract : A dual therapy DNA nanoplatform consisting of spermidine and mammalian target of rapamycin small interfering RNA (mTOR siRNA) is constructed to combat acute lung injury. Both spermidine and mTOR siRNA in the nanoplatform enhance macrophage autophagy and promote macrophage polarization, resulting in synergistic anti‐inflammatory effects in vitro and in acute lung injury mouse model.